Sistem Pendukung Keputusan Pemilihan Program Studi di Politeknik Negeri Padang Menggunakan Metode AHP dan SAW Berbasis Web - Sarah Latifah Marif; Meri Azmi; Alde Alanda (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
The criteria used in the decision support system for the selection of study programs at the Padang State Polytechnic are data obtained from questions in the form of questionnaires. This web-based decision support system uses the Laravel framework and MySQL as the database. The method used in this system is the AHP (Analytic Hierarchy Process) method for weighting the values for each criterion and the SAW (Simple Additive Weighting) method for determining the study program which can produce faster and more subjective data. This decision support system will produce more accurate data and the results obtained are more optimal so that it can help prospective students solve problems in determining which study program to choose according to their abilities by providing advice for decision support